Pendugaan Konsentrasi Klorofil-A Secara Vertikal dengan Neural Network - Syah, Achmad Fachruddin (Universitas Trunojoyo Madura, 2009)
Theprimary production quantity depends on the vertical distribution of chlorophyll concentration in the water column. The chlorophyll maximum value not always observed near or at the sea surface, but sometimes lies deeper than bottom of the euphotic zone. In this case, the ocean color sensors cannot measure the chlorophyll maximum value. A shifted Gauss model has been proposedto describe the variation of the chlorophyll-a (Chl-a) profile which consists offour parameters, i.e.background biomass (Br)1 maximum depth of Chl-a (Zm), total biomass zn the peak (h), and measurenment of the thickness or vertical scale of the peak (o). However, these parameters are not easy to be determined directlyfrom satellite data. therefore, in these research, anANN methodology is used. Using in-situ data 1962 to 1985 in Banda Sea, the above parameters are calculated to derive the Chl-a concentration, sea surface temperature, mixed layer depth, latitude, longi_tude, and season. The total of 53 profiles of Chl-a and temperature are used for ANN. The correlation coefficient of these parameters are 0.852 (B,J, 0.670 (h), 0.983 (d) and 0.990 (Zm) respectively. After comparing with in-situ data and AN!'J model, the result show not good enough agreement relatively.Keywords: Chlorophyll-a (Chl-a), Vertical Structure, Artificial Neural Networks (ANN)